2015
DOI: 10.1016/j.mrfmmm.2015.04.010
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA transcriptome analysis identifies miR-365 as a novel negative regulator of cell proliferation in Zmpste24 -deficient mouse embryonic fibroblasts

Abstract: Zmpste24 is a metalloproteinase responsible for the posttranslational processing and cleavage of prelamin A into mature laminA. Zmpste24-/- mice display a range of progeroid phenotypes overlapping with mice expressing progerin, an altered version of lamin A associated with Hutchinson-Gilford progeria syndrome (HGPS). Increasing evidence has demonstrated that miRNAs contribute to the regulation of normal aging process, but their roles in progeroid disorders remain poorly understood. Here we report the miRNA tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 56 publications
2
15
0
Order By: Relevance
“…It is expressed at high levels in skin squamous cell carcinoma and in some cancer cell lines, and in vivo experiments confirmed that over-expression of mir-365 can promote subcutaneous tumors in mice19. Furthermore, inhibition of mir-365 expression can cause cells to arrest in G1 phase and undergo apoptosis, thus inhibiting the formation of skin tumors2021. However, in recent years, mir-365 has been shown to inhibit cancer.…”
Section: Discussionmentioning
confidence: 99%
“…It is expressed at high levels in skin squamous cell carcinoma and in some cancer cell lines, and in vivo experiments confirmed that over-expression of mir-365 can promote subcutaneous tumors in mice19. Furthermore, inhibition of mir-365 expression can cause cells to arrest in G1 phase and undergo apoptosis, thus inhibiting the formation of skin tumors2021. However, in recent years, mir-365 has been shown to inhibit cancer.…”
Section: Discussionmentioning
confidence: 99%
“…This figure is proposed according to the results obtained on in vitro and in vivo models of accelerated aging syndromes (Jung et al., 2012, 2014; Mariño et al., 2010; Nissan et al., 2012; Ugalde, Español et al., 2011; Ugalde, Ramsay et al., 2011; Xiong et al., 2015; Yu et al., 2013; Zhang et al., 2017)…”
Section: Mirnas In Hereditary Laminopathiesmentioning
confidence: 99%
“…Xiong et al. (2015) generated small RNA libraries from wild‐type and Zmpste24 − / − mouse embryonic fibroblasts (MEF). They identified 10 differentially expressed miRNAs, among which three were upregulated and eight downregulated.…”
Section: Mirnas In Hereditary Laminopathiesmentioning
confidence: 99%
See 2 more Smart Citations